Gingival and oral hygiene conditions in patients with fixed orthodontic appliance wearers - Anggraeni, Rini; Malik, Isnaniyah; Hendiani, Ina (Padjadjaran Journal of Dentistry, 2011)
The aim of this study was to get the description of gingival condition and oral hygiene in patients with the fixed orthodontic appliance at Orthodontics Specialist Clinic of Oral and Dental Hospital Faculty of Dentistry Universitas Padjadjaran (RSGM FKG UNPAD) Bandung. This descriptive study with a survey method included 30 patients with fixed orthodontic appliances consist of 8 male and 22 females. The sample collected by purposive sampling. The data was collected based on filling questioner forms and clinical examination with an assessed degree of gingival enlargement by Carranza assessed Gingival Index by Loe and Silness, measured pocket depth, and assessed Plaque Index by Silness and Loe. The result showed that 90% of samples had gingival enlargement with variants of gingival enlargement degree from grade 1, 2, 3 and mostly present in the posterior area. Prevalence of gingivitis was 100% divided into 76.67% suffering mild gingivitis and 23.33% suffering moderate gingivitis. In an examination of pocket depth, 6.67% had 1.1-2 mm of pocket depth; 70% had 2.1-3 mm of pocket depth, and 23.33% had 3.1-4 mm. In an examination of oral hygiene, 43.33% had good oral hygiene; 46.67% had moderate oral hygiene, and 10% had poor oral hygiene. The conclusion of this research was the orthodontics wearer suffering from gingival enlargement and mild gingivitis.